2022
DOI: 10.1002/app.52799
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Cr (VI) adsorption of functionalized polyimide fibers

Abstract: In order to overcome the shortcomings of nanofiber membranes such as low mechanical properties and poor acid resistance, amino-rich functionalized polyimide (PI)-polyethyleneimine (PEI) fibers were successfully prepared in the study. The structure and morphology in each functionalization step were characterized by scanning electron microscopy (SEM), atomic force microscopy (AFM), static contact angle, attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR), and X-ray photoelectron spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…To further verify the graft of PEI as well as PEG to the polyimide nanofibers, the XPS spectra of the polyimide mats were examined, and the results are shown in Figure . In addition, the different peak locations and the FWHM parameters of N 1s and O 1s are shown in Table S1. Compared to the N 1s and O 1s energy spectra of PI, the peaks of amide, amine, and ammonium obviously increased in the N 1s energy spectrum of PI-PEI (Figure a) and so did the peak of amide in the O 1s energy spectrum of PI-PEI, demonstrating the successful grafting of PEI onto the PI nanofibers. Compared to the O 1s energy spectrum of PI and PI-PEI (Figure b), the peak of the aliphatic ether bond (blue one) in the O 1s energy spectrum of PI-mod significantly increased when PEG was further introduced, demonstrating that PEG was also successfully grafted onto the PI-PEI nanofibers.…”
Section: Resultsmentioning
confidence: 95%
“…To further verify the graft of PEI as well as PEG to the polyimide nanofibers, the XPS spectra of the polyimide mats were examined, and the results are shown in Figure . In addition, the different peak locations and the FWHM parameters of N 1s and O 1s are shown in Table S1. Compared to the N 1s and O 1s energy spectra of PI, the peaks of amide, amine, and ammonium obviously increased in the N 1s energy spectrum of PI-PEI (Figure a) and so did the peak of amide in the O 1s energy spectrum of PI-PEI, demonstrating the successful grafting of PEI onto the PI nanofibers. Compared to the O 1s energy spectrum of PI and PI-PEI (Figure b), the peak of the aliphatic ether bond (blue one) in the O 1s energy spectrum of PI-mod significantly increased when PEG was further introduced, demonstrating that PEG was also successfully grafted onto the PI-PEI nanofibers.…”
Section: Resultsmentioning
confidence: 95%
“…Figure 9 d shows the high-resolution Cr 2p -XPS map. The XPS peaks at 579.98 eV and 583.94 eV binding energy correspond to Cr (VI) in Cr 2 O 7 2− and CrO 4 2− [ 25 ]. However, we found that the binding energy positions of peaks were significantly larger than those of the standard binding energy, indicating that the electrons adsorbed by Cr 2 O 7 2− may have been transferred to F-0.…”
Section: Resultsmentioning
confidence: 99%